Jews history in Morocco and its effect on the current normalization - Benhaouache, Mohamed Nidal (My University, 2022)
This study aims to study unique position between Morocco and the Jews with their historical and cultural background in it, by tracking down their trace in Morocco through the ages and study how the coexistence between the two in both modern and past time. Jews have existed in Morocco since the antiquity, and they are one of the reasons why we consider Morocco as a multicultural nation that sets an example for peaceful coexistence. Furthermore, this study provide the results of such historical collide of the two and how it has chapped the current morocco. The main concern is to explore the effect of this historical cultural clash on the current normalization between the Kingdom of Morocco and the occupied territories of Palestine, and to seek the true reason behind it and how did it emerge from the beginning and whether this Jewish presence has effected it or not.
Keywords: Jewish presence; Multicultural; Morocco; Coexistence; Occupied; territories; Normalization